2018
DOI: 10.1021/acsami.8b13908
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Wettability of Steel Surfaces Processed with Femtosecond Laser Pulses

Abstract: The wettability of a material surface is an essential property that can define the range of applications it can be used for. In the particular case of steel, industrial applications are countless but sometimes limited because of the lack of control over its surface properties. Although different strategies have been proposed to tune the wetting behavior of metal surfaces, most of them require the use of processes such as coatings with different materials or plasma/chemical etching. In this work, we present two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 27 publications
1
54
1
Order By: Relevance
“…[5][6][7][8] The articial fabrication of functional surfaces is not a simply accomplishable task. The dual-scale hierarchical structures with resolution ranging from nano to micro are needed to successfully mimic a particular surface with optical, 9-11 wetting 12,13 or tribological 14,15 properties. Due to the conned laser-matter interaction area, the ultrashort laser pulses gives a possibility to reach a precise structuring in the scale of micrometres by direct laser writing technique via ablation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] The articial fabrication of functional surfaces is not a simply accomplishable task. The dual-scale hierarchical structures with resolution ranging from nano to micro are needed to successfully mimic a particular surface with optical, 9-11 wetting 12,13 or tribological 14,15 properties. Due to the conned laser-matter interaction area, the ultrashort laser pulses gives a possibility to reach a precise structuring in the scale of micrometres by direct laser writing technique via ablation.…”
Section: Introductionmentioning
confidence: 99%
“…The laser-based processes for stainless steel surface wettability control were investigated by ablation of trenches and generation of LIPSS. 13,24 The laser processing parameters, as interline separation for grid patterning and polarisation for LIPSS generation, are proven to be key factors for the fabrication of super-hydrophobic surfaces. The static contact angle coverage for steel via laser structuring is between $90 -150 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also for the particular case of metals, this strategy has allowed its functionalization in an unprecedented manner including, among others, the fine control of surface wettability, the significant reduction in friction and wear, or the fabrication of materials with tailored optical or electrochemical properties. These applications are only a glimpse of what can be achieved with this technology [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of natural surfaces that show properties such as superhydrophobicity as well as the ability to self-clean, including rose petals, reed leaves, and even the skin of some animals (Martinez-Calderon et al, 2016a). It has been fully demonstrated that such superhydrophobicity is decided by both surface chemistry and unique surface micro-nanostructures (Florian et al, 2018), which provides the basic strategy for developing bioinspired superhydrophobic surfaces. In rose petals, the surfaces consist of densely packed microhills covered by a large number of microtrenches, whose wetting regime corresponds to the Wenzel state (Feng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%